Genologia historyczna a stylistyka. Zarys problematyki - Rejter, Artur (Stylistyka, 2021)
The article is dedicated to describing the various liaisons between the historical genology and the stylistics. It is an attempt of theoretical reflection on the subject included in the title of the paper. The authour proves that the both domens are strictly related. One can notice that the most useful stylistics method in genological research are functional stylistics and stylistics of discourse.The functional stylistics is very helpful in analysis of both: the speech genres which are stable in the history of communication and the secondary speech genres distinctly connected with their primary pre-genres. As for discourse stylistics, it can be useful above all in describing the evolution and specifics of contemporary and the newest speech genre phenomena, e.g. the Internet genres.